2003
DOI: 10.1103/physrevlett.91.102502
|View full text |Cite
|
Sign up to set email alerts
|

How to Measure the Spreading Width for the Decay of Superdeformed Nuclei

Abstract: A new expression for the branching ratio for the decay via the E1 process in the normal-deformed band of superdeformed nuclei is given within a simple two-level model. Using this expression, the spreading or tunneling width gamma (downward arrow) for superdeformed decay can be expressed entirely in terms of experimentally known quantities. We show how to determine the tunneling matrix element V from the measured value of gamma (downward arrow) and a statistical model of the energy levels. The accuracy of the t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(39 citation statements)
references
References 7 publications
1
38
0
Order By: Relevance
“…It has been previously noted [2,17] that the model implies a maximum value of F N for any given level. As is evident from Eq.…”
Section: -3mentioning
confidence: 94%
See 3 more Smart Citations
“…It has been previously noted [2,17] that the model implies a maximum value of F N for any given level. As is evident from Eq.…”
Section: -3mentioning
confidence: 94%
“…[8][9][10][11][12][13]), in the present paper we consider only the simple, two-level mixing model first proposed by Stafford and Barrett [1]. In subsequent work, Cardamone, Stafford, and Barrett built on this initial proposal to develop a better physical understanding of the parameters of the model and to introduce statistical approaches leading to the extraction of ND-SD coupling strengths [2]. At the same time, they showed that the inclusion of additional levels does not have a significant impact on measured quantities.…”
Section: A Two-level Mixing Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…SB and Dzyublik and Utyuzh 30) who develop the method of SB further address the lack of knowledge of ∆ by averaging over ∆ assuming a uniform distribution. 31) Cardamone et al 32) on the other hand assume a Wigner distribution, P GOE (∆) = π∆/2 exp(−π∆ 2 /4). The preceding discussion suggests that a Poisson distribution P Poi (∆) = exp(−∆) is more appropriate.…”
Section: §1 Introductionmentioning
confidence: 99%